2021
DOI: 10.1111/cdev.13488
|View full text |Cite
|
Sign up to set email alerts
|

Father Absence in Pregnancy or During Childhood and Pubertal Development in Girls and Boys: A Population‐Based Cohort Study

Abstract: This cohort study, including 15,810 children born 2000–2003 in Denmark, aimed to investigate the association between father absence in pregnancy or during childhood and pubertal development in girls and boys. The children were followed from 11 years of age and throughout pubertal development. Mean age differences according to exposure groups were estimated for each pubertal marker separately and for a combined pubertal marker. The results suggested that father absence in pregnancy and during childhood was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Given that our data on parental composition spanned ages six and older, our findings may support the general claim that midchildhood (juvenility that precedes puberty) is a sensitive period for calibrating sex differences in reproductive strategies [73]. However, without further information from the early childhood or at birth [47], we cannot pinpoint the exact time window when father absence affects pubertal timing. Father absence is associated with different family circumstances, ranging from parental divorce, to the death of the father, to temporary separation due to a parent's job, to co-residence with other family memberseach of which is likely to have different effects on a child's growth and development.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Given that our data on parental composition spanned ages six and older, our findings may support the general claim that midchildhood (juvenility that precedes puberty) is a sensitive period for calibrating sex differences in reproductive strategies [73]. However, without further information from the early childhood or at birth [47], we cannot pinpoint the exact time window when father absence affects pubertal timing. Father absence is associated with different family circumstances, ranging from parental divorce, to the death of the father, to temporary separation due to a parent's job, to co-residence with other family memberseach of which is likely to have different effects on a child's growth and development.…”
Section: Discussionmentioning
confidence: 53%
“…Based on representative and large sample of Korean adolescents, the present study aimed to 1) describe the distribution of age at first nocturnal ejaculation and age at menarche in Korean adolescents; and 2) test the prediction that the onset of puberty was earlier for children living in father-absent households. Among studies that tested the prediction in a population of both sexes, findings have been so far mixed [47][48][49][50][51]. We thus started with the same prediction for both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…11 Further, parental separation in childhood has to our knowledge never been investigated in relation to semen quality. However, in a study examining reproductive development following parental separation, we found that sons exposed to parental separation in childhood entered puberty earlier than their unexposed peers, 26 indicating that parental separation may affect reproductive development. Moreover, the current study aligns with other research, suggesting that stressful life events in childhood may impair male reproductive health.…”
Section: Discussionmentioning
confidence: 82%
“…To address the timing of parental separation in relation to the specific health consequences under investigation, 15 , 16 we further categorized the exposure category of parental separation in childhood according to what was previously seen for parental separation relative to timing of pubertal development. 26 If the children stated that their parents never lived together, they were assigned to the exposure category parental separation from birth . If they stated that their parents separated between the ages of 0–5 years, the children were assigned to the exposure category parental separation in early childhood .…”
Section: Methodsmentioning
confidence: 99%
“…Based on representative and large sample of Korean adolescents, the present study aimed to (i) describe the distribution of age at first nocturnal ejaculation and age at menarche in Korean adolescents; and (ii) test the prediction that the onset of puberty was earlier for children living in father-absent households. Among studies that tested the prediction in a population of both sexes, findings have been so far mixed [ 46–50 ]. We thus started with the prediction for earlier pubertal onset associated with father absence in both sexes.…”
Section: Introductionmentioning
confidence: 99%